Questions and Answers about Aeration - Reed, Carl; Herrman, Tim J.; Higgins, Randall; Harner III, Joseph (My University, 1995)
This publication contains information in a question and answer style about how these devices are used to maintain grain quality.
MF2090_1995_03
Keywords: MF2090; Equipment and structures; Crops; MF